The Relationship Between Working Time and Fatigue of Online Motorcycle Taxi Drivers in Medan - Ramadanil, Ramadanil; Susilawati, Susilawati; Hasibuan, Rapotan (Journal La Medihealtico, 2024)
A common problem among online motorcycle taxi drivers that can negatively affect their health and performance is fatigue. One factor that can reduce the level of fatigue is long working hours. Excessive working time can increase work errors due to increased fatigue and reduced sleep hours. This study aims to determine the effect of working time on fatigue of online motorcycle taxi drivers in the field of struggle. This research is quantitative using observational analytic method with cross sectional approach with univariate and bivariate analysis using chi-square test. The sampling technique with total sampling of 97 online motorcycle taxi riders. This study shows that there is an effect of working time with fatigue in online motorcycle taxi drivers in Medan city with a significance value of 0.00 <0.05. this study is that there is a relationship between the effect of working time and fatigue of online motorcycle taxi drivers in the city of Medan and for online motorcycle taxi drivers in the city of Medan to pay more attention to conditions while working, and not to work late at night. Because it can cause fatigue and worsen their sleep quality so as to develop a degree of health and safety in driving.